Shift-Free Wide-Angle Optical Thin-Film Metamaterial Notch Filter for Visible Laser Protection Systems - Monks, James N. (Cranfield University, 2018)
Poster presented at the 2018 Defence and Security Doctoral Symposium.In recent years, the threat to pilots and other transport vehicles has increased through laser striking. This is due to the ease of accessibility and the low cost of ownership for handheld portable lasers. The reports from the Civil Aviation Authority (CAA) and their American counterpart, the Federal Aviation Administration (FAA), have outlined that visible green laser attacks consist of 83-91% of all incidents [1,2]. This can lead to temporary impairment to the human eye, with consequences increasing with exposure time resulting in retinal and photo-chemical eye damage. Additionally, the magnitude of severity is increased and could lead to fatal collisions. Current efforts for laser protection devices consist of traditional thin-film Rugate filters. This technology is well-established, but has it disadvantages related to the angular intolerance, where the transmission spectrum of the protection filter undergoes a continuous blue-shift to shorter wavelengths as angle of the incident beam increases. The optical and transport industry, as well as government defence agencies, have a desired interest in developing a truly wide-angle (up to 60 degree) and shift-free laser protection system, which is the main drive behind this research. Our research employs a new theoretical approach to the problem and presents an anti-laser striking design that can effectively block out a Class 3B 532 nm green laser. The functional response of the filter achieves an optical density (OD) of 1.88+ for all polarisation states over a wide range of angles up to 85 degrees and attains an integrated visual photopic transmission (IVPT) of 61%. The calculated filter colouration is near-natural, experiencing a slight magenta and turquoise hue for the transmission and reflection colouration, respectively. The devices active blocking layer structure is based on a three-dimensional plasmonic nanocomposite metamaterial, with a base element of silver nanoparticles arranged in a crystallographic primitive hexagonal Bravais lattice planar array, surrounded in a host dielectric medium. The active component is sandwiched between a transparent substrate and an anti-reflection coating. The lattice arrangement enables polarisation insensitivity, with a three dimensional array density catering for an increase attenuation.The designed filter has been computationally verified by a full-wave analysis approach using CST Studio software. The optical properties for refractive indices and extinction coefficients for the used materials have been obtained from literature and adjusted to cater for particle sizing.Reference[1] P. Murphy, “Laser Pointer Safety – Latest aviation statistics”, Laserpointersafety.com, 2017. [Online]. Available: http://www.laserpointersafety.com/latest-stats.html. [Accessed: 18- Aug- 2017].[2] “Laser Incidents reported to the UK CAA 2016,” Laser incidents | UK Civil Aviation Authority. [Online]. Available: https://www.caa.co.uk/Data-and-analysis/Safety-and-security/Datasets/Laser-incidents/. [Accessed: 02- Aug- 2017].
Keywords: 'Optical metamaterials'; 'Laser protection'; 'Wide-angle blocking'; 'DSDS18 poster'; 'DSDS18'; 'Aerospace Engineering not elsewhere classified'